2016
DOI: 10.1039/c6py00664g
|View full text |Cite
|
Sign up to set email alerts
|

Facile and efficient chemical functionalization of aliphatic polyesters by cross metathesis

Abstract: International audienceAn effective preparation of new tailor-made macromolecular materials via a combination of two (atom-efficient) catalytic transformations is reported. First, new aliphatic polyesters with alternated composition have been prepared using a salen aluminum catalyst system. Next, the pendant vinyl moieties in those copolymers have been selectively transformed into various functional groups by metathesis in the presence of homogeneous Grubbs catalysts. The latter metathesis reaction has been opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
1
34
1
Order By: Relevance
“…The monomer is used for copolymerization with CO 2 and with anhydrides . Additionally, bearing a vinyl pendant group as extra functionality, ( R )‐limonene offers the opportunity of postpolymerization modifications to functional polymers . Considering the structural analogies between CHO and LO, we decided to explore the reactivity of the commercially available monomer: the mixture of cis and trans ‐ R ‐limonene oxide in the ROCOP with phthalic anhydride (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer is used for copolymerization with CO 2 and with anhydrides . Additionally, bearing a vinyl pendant group as extra functionality, ( R )‐limonene offers the opportunity of postpolymerization modifications to functional polymers . Considering the structural analogies between CHO and LO, we decided to explore the reactivity of the commercially available monomer: the mixture of cis and trans ‐ R ‐limonene oxide in the ROCOP with phthalic anhydride (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…[28] Additionally,b earing av inyl pendant group as extra functionality,( R)-limoneneo fferst he opportunity of postpolymerization modifications to functional polymers. [29] Considering the structural analogies between CHO and LO, we decided to exploret he reactivity of the commercially availablem onomer:t he mixture of cis and trans-R-limonene oxide in the ROCOP with phthalic anhydride (Scheme 3). Complex 1,a ctivated by DMAP,s howed av ery high activity in bulk allowing an almost quantitative conversion of the monomers in two hours ( Table 4, entry 1).…”
Section: Copolymerization Of Limonene Oxide With Anhydridesmentioning
confidence: 99%
“…While CM has also been used for end-group functionalisation 26,27 and cross-linking for self-healing polymers, 28,29 the development of CM to directly functionalise polymer backbones is of growing importance. 25,[30][31][32][33][34][35][36] To the best of our knowledge Coates et al were the first to propose CM functionalisation of alkene containing polyolefins as a general strategy for developing functional polymer architectures in 2004. 30 The authors synthesised a variety of copolymers, exemplified by polymer 16 (Scheme 7).…”
Section: Post-polymerisation Cross Metathesis For Polymer Functionalimentioning
confidence: 99%
“…In 2016, Thomas and Prunet et al reported the first modification of a polyester via olefin CM. 33 They synthesised copolymers of camphoric anhydride with various olefin containing epoxides, to generate a set of four novel copolymers that contained, in the backbone, Type I, Type II and Type III alkenes. Based on Grubbs' empirical model and catalyst 3, Thomas and Prunet et al coupled the Type II and III alkene polyesters (not shown in Scheme 7) with a reactive Type I cross partner (allyltrimethylsilane).…”
Section: Post-polymerisation Cross Metathesis For Polymer Functionalimentioning
confidence: 99%
“…In this contribution, our focus is on the use of olefin cross‐metathesis (CM) to prepare a family of new monomers. Examples of CM in post‐polymerization modification in the literature are growing . Most recently, we demonstrated the first successful double metathesis on copolymers of lactide and β‐heptenolactone through manipulation of olefin reactivity .…”
Section: Introductionmentioning
confidence: 99%